Language, culture, and society : key topics in linguistic anthropology - Jourdan, Christine; Tuite, Kevin (Cambridge University Press, 2006)
Language, our primary tool of thought and perception, is at the heart of who we are as individuals. Languages are constantly changing, sometimes into entirely new varieties of speech, leading to subtle differences in how we present ourselves to others. This revealing account brings together eleven leading specialists from the fields of linguistics, anthropology, philosophy and psychology, to explore the fascinating relationship between language, culture, and social interaction. A range of major questions are discussed: How does language influence our perception of the world? How do new languages emerge? How do children learn to use language appropriately? What factors determine language choice in bi- and multilingual communities? How far does language contribute to the formation of our personalities? And finally, in what ways does language make us human? Language, Culture and Society will be essential reading for all those interested in language and its crucial role in our social lives. Authors of each chapter are the leading specialists in their field Each chapter gives a fair and unbiased coverage of the issues Raises innovative questions concerning linguistic anthropology